IMPACT OF NLRP3 INFLAMMASOME ON THE DEVELOPMENT OF HYPERTENSION AND RENAL AND CARDIAC HYPERTROPHY IN 2K1C AND DOCA/SALT MICE - Q. Wang; A So; J. Nussberger; J. Tschopp; M. Burnier (The Korean Society of Nephrology, 2012)
NLRP3 inflammasome is formed by NLRP3, the adaptor ASC, and caspase-1, functions as a sensor of danger signals and triggers processing and release of interleukin-1beta (IL-1β). Recent animal studies demonstrate that NLRP3 inflammasome promotes renal inflammation. However, little is known on the role of NLRP3 in hypertension. We have investigated the effect of NLRP3 inflammasome on blood pressure, plasma renin activity and concentration (PRA and PRC), renal and cardiac hypertrophy in NALP3 and ASC deficient mice on which the two-kidney, one clip (2K1C) and the deoxycorticosterone-acetate (DOCA)/salt models were applied. MBP, PRA, PRC, and HW/BW were significantly increased at week 12 in WT-2K1C mice compared to the sham. Neither NLAP3-KO nor ASC-KO 2K1C treated mice developed hypertension and had lower circulating levels of PRA and PRC and serum amyloid A (SAA) and IL6 compared to the control. RNA levels of SAA, NLRP3, IL1β and IL1α were increased in the ischemic kidney in C57BL/6J mice. Administration of anti-IL1β antibody to the WT mice attenuated the increases of blood pressure and renin in 2K1C mice. With chronic administration of DOCA/salt, MBPs in both NLRP3-KO and WT mice were comparable and not significantly increased compared to tap water group. PRA and PRC in both NALP3-KO and WT mice were significantly suppressed by DOCA/salt. HW/BW and KW/BW in both DOCA/salt treated NALP3-KO and WT mice were significantly increased. DOCA/salt induced hypokalemia was comparable between Nlrp3 KO and WT groups. However, the heart and kidney index in DOCA/salt NLRP3-KO mice was significantly lower than that in DOCA/salt WT mice. Our data show that NLRP3 mediated IL1β is linked to development of renovascular hypertension and suggest that a novel target for the treatment of hypertension. The results also implicate that NLRP3 contributes to the development of cardiac and renal hypertrophy independently of blood pressure in the DOCA/salt model.